Morpho-syntactic patterns in spoken Korean English - Rüdiger, Sofia (Varieties of English around the world (VEAW),, 2019)
"Morpho-Syntactic Patterns in Spoken Korean English presents fundamental research on the use of English by South Korean speakers. Despite the extraordinary and vibrant status of the English language in South Korean society (demonstrated, for example, by the notion of English Fever), research on the forms of English in the South Korean context has been sadly neglected in the study of World Englishes. This monograph is the first to provide a rich and contextualized description of the Korean English morpho-syntactic repertoire. It draws on the specifically compiled Spoken Korean English (SPOKE) corpus to shed light on Korean uses of plural marking, articles, pronouns, prepositions, and verbs in spoken English, and demonstrates that English is indeed the language of those who use it. This volume will be highly relevant for researchers interested in Expanding Circle Englishes, Asian Englishes, spoken language corpora, and morpho-syntactic variation"--